2013
DOI: 10.17159/2078-516x/2013/v25i3a361
|View full text |Cite
|
Sign up to set email alerts
|

Injury prevention in football: Knowledge and behaviour of players and availability of medical care in a Nigerian youth football league

Abstract: Background. Exposure to competitive football is increasing among male youth football players in Nigeria. However, medical support to abate the impact of injuries appears inadequate and there is limited literature to show whether youth football players are knowledgeable about, and practise effective measures for injury prevention in football (IPF). Objective. To assess the knowledge and behaviour of male youth football players regarding IPF and the availability of medical care for players. Methods. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Open access in 2015, only 10% of national football associations endorsed the programme. 11 Low end-user awareness and adoption have been reported worldwide, [12][13][14] highlighting the difficulty in successfully disseminating and implementing such interventions. 4 Numerous contextual complexities influence the transfer of findings from research to practice, including individual perceptions, social influences, political pressures and physical demands.…”
Section: Introductionmentioning
confidence: 99%
“…Open access in 2015, only 10% of national football associations endorsed the programme. 11 Low end-user awareness and adoption have been reported worldwide, [12][13][14] highlighting the difficulty in successfully disseminating and implementing such interventions. 4 Numerous contextual complexities influence the transfer of findings from research to practice, including individual perceptions, social influences, political pressures and physical demands.…”
Section: Introductionmentioning
confidence: 99%
“…Among coaches of public high school soccer and basketball teams in Chicago, only 37% agreed to participate in an IPEP trial. 36 Injury prevention knowledge gaps among players, coaches and parents have been identified in both male 37 and female 38 39 amateur soccer communities and also in other team ball sports settings. 14 15 17 In one recent study of youth male soccer players, 79% had not heard of the FIFA 11+.…”
Section: Introductionmentioning
confidence: 99%
“…14 15 17 In one recent study of youth male soccer players, 79% had not heard of the FIFA 11+. 37 Improving IPEP maintenance represents another key challenge in enhancing the impact of IPEPs, but information on programme maintenance is rare. In a systematic review on the reporting of team ball sport IPEP trials, maintenance was the least reported of all implementation aspects.…”
Section: Introductionmentioning
confidence: 99%
“…However, participation in a vigorous sport such as football at the competitive level exposes players to injuries that may blight their careers. The tragedy of a player sustaining a time-loss injury in a developing country such as Nigeria is unimaginable as medical care is very limited [3]. This indicates the need for effective strategies for prevention of injuries.…”
Section: Introductionmentioning
confidence: 99%